2015
DOI: 10.1007/s12011-015-0242-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Comparison of Commercial Selenium Yeast Preparations

Abstract: The trace mineral selenium (Se) is an essential element for human and animal nutrition. The addition of Se to the diet through dietary supplements or fortified food/feed is increasingly common owing to the often sub-optimal content of standard diets of many countries. Se supplements commercially available include the inorganic mineral salts such as sodium selenite or selenate, and organic forms such as Se-enriched yeast. Today, Se yeast is produced by several manufacturers and has become the most widely used s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 73 publications
0
14
0
4
Order By: Relevance
“…Indeed, the fraction of water-soluble Se in various yeasts varies from 11.5% up to 28.0% (Encinar et al, 2003). It has been confirmed that significant differences exist between Se-yeast products in terms of Se deposition in different cell fractions and Se bioavailability (Fagan et al, 2015).…”
Section: Se-yeast: Advantages and Disadvantagesmentioning
confidence: 88%
“…Indeed, the fraction of water-soluble Se in various yeasts varies from 11.5% up to 28.0% (Encinar et al, 2003). It has been confirmed that significant differences exist between Se-yeast products in terms of Se deposition in different cell fractions and Se bioavailability (Fagan et al, 2015).…”
Section: Se-yeast: Advantages and Disadvantagesmentioning
confidence: 88%
“…The bioavailability and biological activity of selenium depend not only on the total ingested amount, but also on its chemical form, solubility, digestibility and accessibility, the presence of other dietary components, and the physiological status of the organism [ 25 , 80 , 81 ]. The organic forms are less toxic and are absorbed more effectively (especially SeMet) than the inorganic ones [ 82 , 83 ].…”
Section: Conventional and Next-generation Selenium Dietary Supplemmentioning
confidence: 99%
“…The differences imply that the preparations also differ in properties such as bioavailability, bio-efficacy, shelf-life, toxicology, etc. Based on LC–MS/MS and quantitative proteomics, they identified over 62 Se-containing proteins [ 25 ]. Torula yeast ( Candida utilis ) seems to metabolize Se in a specific way, different from Brewer’s yeast ( Saccharomyces cerevisiae ), where the most abundant compound is selenohomolanthionine (SeHLan) [ 87 ].…”
Section: Conventional and Next-generation Selenium Dietary Supplemmentioning
confidence: 99%
See 2 more Smart Citations